1986
DOI: 10.1002/jpln.19861490407
|View full text |Cite
|
Sign up to set email alerts
|

The Nmin‐method – an aid to integrating various objectives of nitrogen fertilization

Abstract: There is increasing interest in the rate and timing of N-fertilization from both an economical and an ecological point of view. Fertilizer recommendations for a variety of aims can be made using the N,,,-method, as shown by experiments on deep rootable loess loam soils.Yields of cereal crops and sugar were increased by 2-3 dtiha by application of the N,,-method. The N,,,-method led to a reduction in the rate of fertilizer application by 30 kg N h a with sugar beet.Any stipulated NO3 level in leaf vegetables ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 6 publications
0
22
1
Order By: Relevance
“…Determination of soil mineral N content in spring (i.e., N min test) (Wehrmann and Scharpf 1986) measures one component of soil N supply. The pre-sidedress soil nitrate test (Magdoff 1991) provides an index of relative soil N supply through measurement of soil NO 3 -N content early in the growing season.…”
mentioning
confidence: 99%
“…Determination of soil mineral N content in spring (i.e., N min test) (Wehrmann and Scharpf 1986) measures one component of soil N supply. The pre-sidedress soil nitrate test (Magdoff 1991) provides an index of relative soil N supply through measurement of soil NO 3 -N content early in the growing season.…”
mentioning
confidence: 99%
“…Spring soil inorganic N measurements have been used in making fertilizer N recommendations for potato in some potato production areas, for example in Germany (Wehrmann and Scharpf 1986). However, Bélanger et al (2001) concluded that preplant measurement of soil NO 3 content, or soil inorganic N content, did not adequately predict the optimal fertilizer N rate for potato in Atlantic Canada when used alone.…”
mentioning
confidence: 99%
“…However, the measurement of the magnitude of the soil mineral nitrogen (SMN) pool accessible to plant roots is not very reliable when there are periods with high rainfall during the growing season, or under high temperatures, or in soils with high organic matter contents (Wehrmann and Scharpf 1986). Stoniness is also a factor, as laboratory results in milligrams per kilogram need to be converted to kilograms per hectare to a given sample depth using an assumed bulk density for the soil.…”
Section: Methods Based On Soil Mineral N Contentmentioning
confidence: 99%
“…In the Nmin method (Wehrmann and Scharpf 1986), the N-fertiliser requirement of the crop (N rate ) is estimated as N rate = N target − N min . N target is a specific target level of nitrogen that must be available for maximum growth and yield to occur (Feller and Fink 2002); the target value is determined experimentally and takes into account both nitrogen already in the soil and nitrogen supplied by the application of fertilisers.…”
Section: Methods Based On Soil Mineral N Contentmentioning
confidence: 99%